Biology Learning Innovation to Support Sustainable Development Program: A Systematic Literature Review (2019-2024) - Ulya Ruwaida; Zevira Fransisca Aurora; Opik Prasetyo; Hery Fajeriadi; Rina Oktaviana; Nurul Aulia (Journal of Mathematics Science and Computer Education, 2026)
Learning innovation is one of the important things that must be done in biology learning activities. Learning innovation is also very important to support sustainable development programs, especially for indicators of improving the quality of education. This study aims to analyze the development trend of innovation in biology learning to support sustainable development programs through a literature review. The research method used the PRISMA systematic review approach through a comprehensive literature search from the Google Scholar database. The inclusion criteria in this study were that articles were taken from the Google Scholar database in the period 2019-2024, articles were relevant to the research topic and field of biology, and articles were available in full access, while the exclusion criteria were the opposite of the inclusion criteria. The initial identification resulted in 43 articles, which then went through the evaluation and content analysis stages, resulting in 9 articles. Articles were analyzed based on year of publication, type of innovation, and level of education. The novelty of this article lies in its comprehensive mapping of innovations in biology education with the Sustainable Development Goals (SDGs), as well as the development of an integrative framework that links biology competencies and sustainability competencies. The findings of the literature review revealed that the trend of developing innovations in biology learning increased significantly. Innovation is proven to be able to support sustainable development programs in terms of improving the quality of education and managing environmental sustainability. Learning innovation is dominated by the development of learning resources in the form of teaching materials for students. This finding also shows that the publication of innovation studies has been carried out at various levels of education equally. The contribution of this study is expected to provide recommendations and motivation for teachers to integrate the latest innovations in biology learning activities while supporting sustainable development programs at various levels of education.